Family Support And Social Support In Pre-Operative Anxiety Status - Alva Cherry mustamu; Difran Nobel Bistara; Susanti (Jurnal Ilmiah Kesehatan, 2023)
Anxiety is vital in determining the decision of appendectomy surgery. Anxiety may be reduced with support from family and society. This study aimed to analyze the relationship between family and social support on the anxiety of preoperative appendectomy patients. This study used an analytical descriptive quantitative method with a cross-sectional approach on 15 preoperative appendectomy patients in the operating room. Collecting data was using a questionnaire from one month. Data analysis was using Spearman rank test. The study’s results indicate that family support has a significant value of 0.904 for anxiety, while social support has a significant value of 0.059. This study shows that family and social support do not affect the anxiety status of preoperative appendectomy patients. Therefore, future research on the current topic is recommended but with a larger sample to prove the hypothesis.